Differences in Neurocognitive Impairment Among HIV-Infected Latinos in the United States. (6th September 2017) - Marquine, María J.; Heaton, Anne; Johnson, Neco; Rivera-Mindt, Monica; Cherner, Mariana; Bloss, Cinnamon; Hulgan, Todd; Umlauf, Anya; Moore, David J.; Fazeli, Pariya; Morgello, Susan; Franklin, Donald; et al.
Abstract: Objectives: Human immunodeficiency virus (HIV) disproportionately affects Hispanics/Latinos in the United States, yet little is known about neurocognitive impairment (NCI) in this group. We compared the rates of NCI in large well-characterized samples of HIV-infected (HIV+) Latinos and (non-Latino) Whites, and examined HIV-associated NCI among subgroups of Latinos.Methods: Participants included English-speaking HIV+ adults assessed at six U.S. medical centers (194 Latinos, 600 Whites). For overall group, age: M =42.65 years, SD =8.93; 86% male; education: M =13.17, SD =2.73; 54% had acquired immunodeficiency syndrome. NCI was assessed with a comprehensive test battery with normative corrections for age, education and gender. Covariates examined included HIV-disease characteristics, comorbidities, and genetic ancestry.Results: Compared with Whites, Latinos had higher rates of global NCI (42% vs . 54%), and domain NCI in executive function, learning, recall, working memory, and processing speed. Latinos also fared worse than Whites on current and historical HIV-disease characteristics, and nadir CD4 partially mediated ethnic differences in NCI. Yet, Latinos continued to have more global NCI [odds ratio (OR)=1.59; 95% confidence interval (CI)=1.13–2.23; p <.01] after adjusting for significant covariates. Higher rates of global NCI were observed with Puerto Rican ( n =60; 71%) versus Mexican ( n =79, 44%) origin/descent; this disparity persisted in models adjusting for significant covariates (OR=2.40; CI=1.11–5.29; p =.03).Conclusions : HIV+ Latinos, especially of Puerto Rican ( vs . Mexican) origin/descent had increased rates of NCI compared with Whites. Differences in rates of NCI were not completely explained by worse HIV-disease characteristics, neurocognitive comorbidities, or genetic ancestry. Future studies should explore culturally relevant psychosocial, biomedical, and genetic factors that might explain these disparities and inform the development of targeted interventions. ( JINS, 2018, 24, 163–175)